Modification of gut microbiota in the treatment of childhood obesity - Bała, Kamila; Staszko, Natalia (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Childhood obesity is recognized as the most common chronic disease of childhood and adolescence, associated with metabolic disturbances and alterations in the gut microbiome. Research indicates that modulation of the gut microbiota may play a pivotal role in obesity management. This review summarizes current strategies for influencing the pediatric gut microbiome, including probiotics, prebiotics, synbiotics, chitosan, fecal micro- biota transplantation, metformin, dietary interventions and physical activity. The applied gut microbiome modifications contribute to an increase in beneficial bacterial populations while simultaneously reducing harmful bacterial populations. These changes enhance the production of short-chain fatty acids and decrease inflammation, ultimately leading to improved metabolic outcomes and weight reduction in pediatric patients. Modulating the gut microbiome represents a promising approach for treating obesity, however, long-term studies involving large populations are needed to confirm the efficacy and safety of these interventions in children.